Th17 down-regulation is involved in reduced progression of schistosomiasis fibrosis in ICOSL KO mice. - Bo Wang; Song Liang; Yu Wang; Xing-Quan Zhu; Wei Gong; Hui-Qin Zhang; Ying Li; Chao-Ming Xia (Public Library of Science (PLoS), 2015)
Granulomatous and fibrosing inflammation in response to parasite eggs is the main pathology that occurs during infection with Schistosoma spp. CD4+ T cells play critical roles in both host immune responses against parasitic infection and immunopathology in schistosomiasis,and coordinate many types of immune cells that contribute to fibrosis. ICOSL plays an important role in controlling specific aspects of T cell activation, differentiation, and function. Previous work has suggested that ICOS is essential for Th17 cell development. However, the immunopathogenesis of this pathway in schistosomiasis fibrosisis still unclear.Using models of schistosomiasis in ICOSL KO and the C57BL/6 WT mice, we studied the role of the ICOSL/ICOS interaction in the mediation of the Th17 response in host granulomatous inflammation, particularly in liver fibrosis during S. japonicum infection, and investigated the immune responses and pathology of ICOSL KO mice in these models. The results showed that ICOSL KO mice exhibited improved survival, reduced liver granulomatous inflammation around parasite eggs, markedly inhibited hepatic fibrosis development, lower levels of Th17-related cytokines (IL-17/IL-21), Th2-related cytokines (IL-4/IL-6/IL-10), a pro-fibrotic cytokine (IL-13), and TGF-β1, but higher level of Th1-related cytokine (IFN-γ) compared to wild-type (WT) mice. The reduced progression of fibrogenesis was correlated with the down-regulation of Th17 and Th2 and the elimination of ICOSL/ICOS interactions.Our findings suggest that IL-17-producing cells contribute to the hepatic granulomatous inflammation and subsequent fibrosis. Importantly, there was a clearly positive correlation between the presence of IL-17-producing cells and ICOS expression in ICOSL KO mice, and additional results indicated that Th17 was involved in the pathological tissue remodeling in liver fibrosis induced by schistosomiasis.